Effect of different base material for spawn production of new strain IGKVm-11 of oyster mushroom (Pleurotus sp.) - Patel, Gopal; Chandrawanshi, S S; Awadhiya, G K (Mushroom Research, 2016)
The effect of different base materials viz. sorghum, bajra, ragi, kutki, kodo, wheat, maize and paddy grains on the production of spawn of new strain IGKVm-11 of oyster mushroom (Pleurotus sp.) was studied.Â  The minimum period for spawn development was recorded in sorghum grains (10.00 days) followed by Bajra (11.00 days) grains and maximum period for spawn development was recorded in paddy grains (20.00 days) followed by Maize (19.00 days). The results clearly demonstrated that between different base materials used for spawn production, maximum growth rate were recorded on sorghum grains. The second best grain for spawn production of new strain IGKVm-11 of oyster mushroom (Pleurotus sp.) was on bajra grains.Â